2018
DOI: 10.3892/ol.2018.9477
|View full text |Cite
|
Sign up to set email alerts
|

The effect of centromere protein U silencing by lentiviral mediated RNA interference on the proliferation and apoptosis of breast cancer

Abstract: Centromere protein U (CENPU) is a novel transcriptional repressor that is associated with different types of cancer. However, its function in breast cancer is poorly understood. In the present study, it was identified that CENPU was highly expressed in breast cancer tissues compared with expression in normal breast tissues (P=0.001). Furthermore, the CENPU mRNA level in tumors was often elevated, compared with the matched adjacent normal breast cancer tissue specimens in the dataset from The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Intriguingly, 3 of the best 21 ranked predicted TSGs, bibliographic search provided clues that they indeed play a role in cancer, but that they would rather behave as OG. These genes are CENPU [59], FXYD2 [60], ANXA9 [61]. In fact, the literature provides other examples of genes able to switch from oncogenes to tumor suppressor genes, depending on the context [62], which could be the case for these genes.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, 3 of the best 21 ranked predicted TSGs, bibliographic search provided clues that they indeed play a role in cancer, but that they would rather behave as OG. These genes are CENPU [59], FXYD2 [60], ANXA9 [61]. In fact, the literature provides other examples of genes able to switch from oncogenes to tumor suppressor genes, depending on the context [62], which could be the case for these genes.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the impact of CENP-U in tumorigenesis of breast cancer cells, we used CENP-U siRNA plasmids to establish stable CENP-U depletion cells. Previous data indicated that CENP-U was highly expressed in the MDA-MB-231 and MCF-7 cells (35,36). Therefore, we established stable CENP-U depletion in MDA-MB-231, MCF-7 cells (231-shCENP-U/MCF-7-shCENP-U) and the negative control cells (231-shControl/MCF-7-shCcontrol).…”
Section: Depletion Of Cenp-u Expression Inhibits Breast Cancer Cell Pmentioning
confidence: 98%
“…According to previous studies, CENPU is implicated in kinetochore assembly, mitotic progression, and segregation of chromosomes [ 6 , 7 ]. Our previous study demonstrated that CENPU downregulation might inhibit the proliferation of human breast cancer cells [ 8 ]. However, molecular mechanisms underlying that observation remain undetermined.…”
Section: Introductionmentioning
confidence: 99%